Unfit, Unwanted, or Superfluous? State Agricultural Farms and Their Workers as a New Social and Occupational Group in the Polish People’s Republic - Szpak, Ewelina (Historical Studies on Central Europe, 2025)
State agricultural farms (Państwowe Gospodarstwa Rolne or PGR in Polish) had a unique socio-economic status in post-war Poland. Modelled on the Soviet sovkhozes, they were intended to serve as a space for the creation of a new socialist socio-professional group, described in official propaganda as “the most advanced rural segment of the working class.” Although designed as a tool for agricultural modernization, state farms ultimately became spaces of permanent marginalization and lack of prospects, with far-reaching consequences for their communities up to the end of the People’s Republic of Poland (PRL). Located between the traditional rural and working-class communities, state-farm workers were seen by public perception both as beneficiaries of the communist transformation and a microcosm of all the social pathologies, leading to their social rejection and stigmatisation. This article examines the emergence of agricultural workers in the Polish People’s Republic as a distinct social and occupational group, considering their low status, lack of integration with other occupational groups, and gradual marginalization. Drawing on archival material, journalistic sources, and oral testimonies, it examines how workers on state farms functioned in the Polish People’s Republic, how their work and lifestyles were perceived, and how their systemic organization limited their agency and social mobility. The text also addresses the issue of the social isolation of agricultural workers, who after the collapse of communism were seen as an example of the failed attempt to create the communist ‘new man.’